This skin was once mine and other disturbances - LaRocca, Eric (Titan Books, 2024)
"This Skin Was Once Mine : When her father dies under mysterious circumstances, Jillian Finch finds herself grieving the man she idolized while struggling to feel comfortable in the childhood home she was sent away from nearly twenty years ago. Then Jillian discovers a dark secret that will threaten to undo everything she has ever known about her father. -- Seedling : A young man's father calls him early in the morning to say that his mother has passed away. He arrives home to find his mother's body still in the house. Struggling to process what has happened he notices a small black wound appear on his wrist. Then he discovers his father is cursed with the same affliction. -- All the Parts of You That Won't Easily Burn : Enoch Leadbetter goes to buy a knife for his husband to use at a forthcoming dinner party. He encounters a strange shopkeeper who draws him into an intoxicating new obsession and sets him on a path towards mutilation and destruction... -- Prickle : Two old men revive a cruel game with devastating consequences..." --